PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN LITERASI SAINS SISWA DI SMPN 11 SURABAYA - Ali Akbar; An Nuril Maulida Fauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze improvements in students’ science literacy following the implementation of the discovery learning model. The research design used is a pre-experimental design, specifically a one-group pretest-posttest design. The research subjects were students in class IX-G at SMPN 11 Surabaya. The research instruments used were pretests and posttests. The data analysis techniques used were the normality test, t-test, and N-Gain test. The average N-Gain score obtained was 0.50, which falls into the moderate improvement category. Meanwhile, the N-Gain percentage for all students showed that 11% of students experienced improvement in the high category. A total of 75% showed moderate improvement. Meanwhile, the remaining 14% of students had low N-Gain scores. Thus, it can be concluded that the application of the discovery learning model can improve students’ science literacy. A suggestion for future research is that this model could be applied to different subject materials or educational levels.